Classification of several demosponge (Demospongiae, Porifera) taxa re-evaluated with DNA barcodes of type (and other) specimens - Erpenbeck, Dirk; Voigt, Oliver; Möx, Andreas; Galitz, Adrian; Gölitz, Sebastian; Lüter, Carsten; Patzelt, Tanja; Hofe, Theresa Vom; Wendel, Sarah; Wörheide, Gert; Soest, Rob W.m. Van (Zootaxa, 2026)
Demosponge classification is notoriously challenged by the paucity of informative morphological characters with sufficient complexity to discriminate between apomorphies and convergences. Molecular data, preferably from type material, helps shed light on phylogenetic relationships. In the following, we review, based on the results of DNA barcoding of type (and other) material, the classification of several demosponge species and genera with either eminent or previously uncertain classification. We report that the aster-bearing genus Leptosastra Topsent, 1904, is a poecilosclerid, unlike Clathria faviformis Lehnert & van Soest, 1996, which should be classified as Raspailiidae. The genus transfers of Eurypon laughlini Díaz, Alvarez & van Soest, 1987 to Prosuberites Topsent, and Leucophloeus lewisi Van Soest & Stentoft, 1988, to Axinyssa Lendenfeld are supported, unlike the transfer of Halichondria almae (Carballo, Uriz & García-Gómez, 1996) from Ciocalapata de Laubenfels. The new sequences are the first to be published in the new version of the Sponge Barcoding Database (SBDv2) of the Sponge Barcoding Project (www.spongebarcoding.org). Our findings underline the benefits of sequencing historic reference material, even if it is centuries old, and emphasises that type material should always be considered in answering systematic questions, particularly with challenging taxa such as sponges.